The Role of Financial Management in the Effectiveness of Entrepreneurship Training Programs for MSMEs in Bekasi City - Nathasya, Stella; Setyanto, Eddy; Muhammad, Muhammad; Oktaviany, Venny (STIE Tri Bhakti, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, including Bekasi City which serves as a vital hub for trade and services. Despite their significant contributions to employment generation and income distribution, many MSME actors continue to face fundamental challenges in financial management, such as the absence of routine bookkeeping, the mixing of personal and business finances, and limited ability to prepare simple cash flow statements and budgets. These weaknesses often lead to liquidity problems, misallocation of working capital, and restricted access to formal financing, thereby affecting business sustainability. This study aims to analyze the role of financial management in improving the effectiveness of entrepreneurship training, particularly in fostering financial behavioral change among MSMEs in Bekasi. The research employed a qualitative descriptive approach through interviews, observations, and document studies, and the data were analyzed using an interactive model. The findings indicate that integrating cash flow planning, budgeting, simple bookkeeping, and financial evaluation modules into the training curriculum had a positive impact on participants’ financial literacy. Indicators of improvement include increased regularity in transaction recording, more disciplined budget preparation, and clearer separation of personal and business finances. Training effectiveness was further enhanced through case-based learning, direct practice, and post-training mentoring; participants who received 3–6 months of mentoring demonstrated higher consistency in financial record-keeping compared to those who only attended short-term training. Moreover, the introduction of digital financial literacy through mobile-based bookkeeping applications accelerated the adoption of modern financial practices. The study concludes that training effectiveness is not solely determined by module design, but also by social and institutional support that connects MSMEs with their supporting ecosystem. These findings contribute to the development of a collaborative training model that integrates digital financial literacy and sustainable mentoring to strengthen MSME financial resilience and competitiveness in both local and regional markets.